Molecular cloning, characterization and expression profile of a glutathione peroxidase-like thioredoxin peroxidase (TPxGl) of the rodent malaria parasite Plasmodium berghei. Issue 3 (June 2015) - Haselton, Kyle J.; David, Robin; Fell, Katherine; Schulte, Emily; Dybas, Matthew; Olsen, Kenneth W.; Kanzok, Stefan M.
Abstract: Glutathione peroxidases (GPx) comprise an important group of redox active proteins with diverse functions, including antioxidant defense and signaling. Although the genome of the malaria parasite Plasmodium does not contain a genuine GPx gene a glutathione peroxidase-like thioredoxin peroxidase (TPxGl ) has recently been identified and biochemically characterized in the human malaria parasite P. falciparum . To gain more insight into the potential biological function of this enzyme we have cloned and expressed TPxGl of the rodent model system P. berghei (PbTPxGl ). Biochemical characterization confirmed that the protein is redox active with the P. berghei thioredoxin system. We compared PbTPxGl to recently characterized thioredoxin-dependent GPx-type proteins of other organisms, and generated the first hypothetical 3D model of a Plasmodium TPxGl, which shows the conservation of the thioredoxin-fold as well as the spatial orientation of a classic GPx catalytic tetrad. In vivo studies indicate that PbTPxGl is continuously expressed in all P. berghei asexual blood stages, gametocytes and in early mosquito-stage parasites. Confocal microscopy suggest a cytoplasmic localization of PbTPxGl in all investigated parasite life stages, specifically in mature ookinetes. Our data provides new insights into the structure and ubiquitous expression of Plasmodium TPxGl and warrants further investigation into this potentially important redox enzyme. Graphical abstract: Highlights: Characterization of a glutathione peroxidase-like TPx of P. berghei (PbTPxGl ) PbTPxGl is active with the P. berghei Trx-system and displays antioxidant activity. Hypothetical 3D model shows structural relationship with GPx from other organisms. PbTPxGl is expressed in the cytoplasm of asexual, sexual and ookinete stages.